Sensitization of colonic nociceptors by TNFα is dependent on TNFR1 expression and p38 MAPK activity. (21st July 2022) - Barker, Katie H.; Higham, James P.; Pattison, Luke A.; Taylor, Toni S.; Chessell, Iain P.; Welsh, Fraser; Smith, Ewan St. J.; Bulmer, David C.
Abstract : Abstract: Visceral pain is a leading cause of morbidity in gastrointestinal diseases, which is exacerbated by the gut‐related side‐effects of many analgesics. New treatments are needed and further understanding of the mediators and mechanisms underpinning visceral nociception in disease states is required to facilitate this. The pro‐inflammatory cytokine TNFα is linked to pain in both patients with inflammatory bowel disease and irritable bowel syndrome, and has been shown to sensitize colonic sensory neurons. Somatic, TNFα‐triggered thermal and mechanical hypersensitivity is mediated by TRPV1 signalling and p38 MAPK activity respectively, downstream of TNFR1 receptor activation. We therefore hypothesized that TNFR1‐evoked p38 MAPK activity may also be responsible for TNFα sensitization of colonic afferent responses to the TRPV1 agonist capsaicin, and noxious distension of the bowel. Using Ca 2+ imaging of dorsal root ganglion sensory neurons, we observed TNFα‐mediated increases in intracellular [Ca 2+ ] and sensitization of capsaicin responses. The sensitizing effects of TNFα were dependent on TNFR1 expression and attenuated by p38 MAPK inhibition. Consistent with these findings, ex vivo colonic afferent fibre recordings demonstrated an enhanced response to noxious ramp distention of the bowel and bath application of capsaicin following TNFα pre‐treatment. Responses were reversed by p38 MAPK inhibition and absent in tissue from TNFR1 knockout mice. Our findings demonstrate a contribution of TNFR1, p38 MAPK and TRPV1 to TNFα‐induced sensitization of colonic afferents, highlighting the potential utility of these drug targets for the treatment of visceral pain in gastrointestinal disease. Key points: The pro‐inflammatory cytokine TNFα is elevated in gastrointestinal disease and sensitizes colonic afferents via modulation of TRPA1 and NaV 1.8 activity. We further develop this understanding by demonstrating a role for p38 MAPK and TRPV1 in TNFα‐mediated colonic afferent sensitization. Specifically, we show that: TNFα sensitizes sensory neurons and colonic afferents to the TRPV1 agonist capsaicin. TNFα‐mediated sensitization of sensory neurons and colonic nociceptors is dependent on TNFR1 expression. TNFα sensitization of sensory neurons and colonic afferents to capsaicin and noxious ramp distension is abolished by inhibition of p38 MAPK. Collectively these data support the utility of targeting TNFα, TNFR1 and their downstream signalling via p38 MAPK for the treatment of visceral pain in gastrointestinal disease. Abstract : Abstract figure legend TNFα sensitized Ca 2+ responses to the TRPV1 agonist capsaicin in dorsal root ganglion sensory neurons. Sensitization was TNFR1‐dependent and attenuated by inhibition of p38 MAPK. Direct Ca 2+ responses to TNFα were TRPV1 dependent. In ex vivo colonic afferent recordings, TNFα increased sensitivity to noxious ramp distension and capsaicin, both of which were absent in TNFR1 –/– tissue or blocked by inhibition of p38 MAPK. These findings establish a role for TNFR1, p38 MAPK and TRPV1 in TNFα‐mediated sensitization of colonic afferents.